2009
DOI: 10.1242/dev.026427
|View full text |Cite
|
Sign up to set email alerts
|

A proximal conserved repeat in theXistgene is essential as a genomic element for X-inactivation in mouse

Abstract: X-inactivation in female mammals is triggered by the association of non-coding Xist RNA in cis with the X chromosome. Although it has been suggested that the A-repeat located in the proximal part of the Xist RNA is required for chromosomal silencing in ES cells, its role in mouse has not yet been addressed. Here, we deleted the A-repeat in mouse and studied its effects on X-inactivation during embryogenesis. The deletion, when paternally transmitted, caused a failure of imprinted X-inactivation in the extraemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 34 publications
7
139
0
2
Order By: Relevance
“…Since our previous study revealed that a simple deletion of the A-repeat abolished Xist upregulation during embryonic development (Hoki et al, 2009), we decided instead to express Xist RNA lacking the A-repeat using a CAG promoter, using the same approach as we used previously to create the Xist CAG allele (Amakawa et al, 2015). The 5′ region of Xist spanning from its endogenous promoter to the XhoI site 0.9 kb downstream of the major transcription start site in exon 1 was replaced with a fragment containing the CAG promoter and a floxed selection marker by gene targeting to generate the Xist CAGΔ5′-2L allele (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Since our previous study revealed that a simple deletion of the A-repeat abolished Xist upregulation during embryonic development (Hoki et al, 2009), we decided instead to express Xist RNA lacking the A-repeat using a CAG promoter, using the same approach as we used previously to create the Xist CAG allele (Amakawa et al, 2015). The 5′ region of Xist spanning from its endogenous promoter to the XhoI site 0.9 kb downstream of the major transcription start site in exon 1 was replaced with a fragment containing the CAG promoter and a floxed selection marker by gene targeting to generate the Xist CAGΔ5′-2L allele (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has been suggested that this apparent discrepancy is reconciled by the finding that X-linked genes that fail to be silenced are located at the outside or periphery of the cloud formed by the Xist RNA lacking the A-repeat, and are therefore not incorporated into the apparent heterochromatin domain (Chaumeil et al, 2006), although the molecular basis of how the A-repeat exerts its effect on this spatiotemporal regulation is not known. When we previously attempted to explore this issue by targeted deletion of the A-repeat in mouse, it completely abolished the expression of Xist, precluding evaluation of the RNA lacking the A-repeat (Hoki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the A-repeat in the endogenous locus has been examined in the mouse. A mutant allele, Xist DA , was produced by gene targeting [37]. Males and females hemizygous and heterozygous, respectively, for Xist DA , which is maternal in origin, were produced but intercrosses between those males hemizygous for Xist DA and wild-type females revealed that the majority of female offspring, all of which should have inherited the Xist DA allele, were lost soon after implantation.…”
Section: Functional Domains Of Xist Rnamentioning
confidence: 99%
“…MEETING REVIEW Development 138 (23) One interesting feature of Xist discussed at this meeting concerned the highly conserved A-repeat region located in the proximal part of the transcript. Previous work from Anton Wutz had shown that this region is necessary for Xist RNA to establish gene silencing during XCI (Wutz et al, 2002), and the Sado laboratory had reported that this region acts as a positive regulatory element for Xist expression (Hoki et al, 2009). This region has also been reported to produce a short independent transcript called RepA (Zhao et al, 2008).…”
Section: Teasing Apart the Xist Regulatory Networkmentioning
confidence: 99%